Food Legumes and Rising Temperatures: Effects, Adaptive Functional Mechanisms Specific to Reproductive Growth Stage and Strategies to Improve Heat Tolerance - Sita, Kumari; Sehgal, Akanksha; HanumanthaRao, Bindumadhava; Nair, Ramakrishnan M.; Vara Prasad, P. V.; Kumar, Shiv; Gaur, Pooran M.; Farooq, Muhammad; Siddique, Kadambot H. M.; Varshney, Rajeev K.; Nayyar, Harsh (Frontiers in Plant Science, 2017)
Ambient temperatures are predicted to rise in the future owing to several reasons associated with global climate changes. These temperature increases can cause heat stress- a severe threat to crop production in most countries. Legumes are well-known for their impact on agricultural sustainability as well as their nutritional and health benefits. Heat stress imposes challenges for legume crops and has deleterious effects on the morphology, physiology and reproductive growth of plants. High-temperature stress during the reproductive stage is becoming a serious constraint to the productivity of grain legumes as their cultivation expands to warmer environments and temperature variability increases due to climate change. The reproductive period is vital in the life cycle of all plants and is susceptible to high-temperature stress as various metabolic processes are adversely impacted during this phase, which reduces crop yield. Food legumes exposed to high-temperature stress during reproduction show flower abortion, pollen and ovule infertility, impaired fertilization, and reduced seed filling, leading to smaller seeds and poor yields. Through various breeding techniques, heat tolerance in major legumes can be enhanced to improve performance in the field. Omics approaches unravel different mechanisms underlying thermotolerance, which is imperative to understand the processes of molecular responses towards high-temperature stress.